Influence of Antimony Oxide on Epoxy Based Intumescent Flame Retardation Coating System - , Riyazuddin (Polymers (Basel), 2020)
Ethylenediamine modified Ammonium polyphosphate (EDA-MAPP), and Charring-Foaming Agents (CFA) was prepared via a simple chemical approach and further utilizes for the preparation of Epoxy resin based intumescent flame retardation coatings. The ratio belongs to MAPP and CFA was fixed at 2:1 ratio. Comparative thermo gravimetric analysis TGA study of Modified Ammonium polyphosphate (MAPP) and Ammonium polyphosphate (APP) investigated. Sb(2)O(3) was introduced into flame retardation coating formulation at various amounts to evaluate the synergistic action of Sb(2)O(3) along with flame retardant coating system. The synergistic action of Sb(2)O(3) on flame retardation coating formulation was studied by vertical burning test (UL-94V), thermo gravimetric analysis (TGA), Limited Oxygen Index (LOI), and Fourier Transform Infra-Red spectroscopy (FTIR). The UL-94V results indicated that adding Sb(2)O(3) effectively increased flame retardancy and meets V-0 ratings at each concentration. The TGA results revealed that the amalgamation of Sb(2)O(3) at each concentration effectively increased the thermal stability of the flame retardant coating system. Cone-calorimeter study results that Sb(2)O(3) successfully minimized the combustion parameters like, Peak Heat Release Rate (PHRR), and Total Heat Release (THR). The FTIR result shows that Sb(2)O(3) can react with MAPP and generates the dense-charred layer which prevents the transfer of heat and oxygen.